Discrete Event Simulation-Based Reliability Evaluation of a Traffic Signal Controller - Jang, Joong Soon; Park, Sang C. (Modelling and Simulation in Engineering, 2018)
A mission reliability evaluation methodology for a signal traffic controller is presented in this paper. To develop the new evaluation methodology, this paper combines the Discrete Event System Specification (DEVS) formalism which has been popular in manufacturing area for three reasons: (1) its features compatible with the object-oriented modeling; (2) its rigorous formal definition; and (3) its support for the specifications of discrete event models in a hierarchical and modular manner. By using the DEVS formalism, we construct a simulation model which takes into account not only the characteristics of a traffic signal controller but also the operating environment. Once a model is constructed, it is possible to perform simulation experiments. The proposed methodology computes the mission reliability of a traffic signal controller by using a simulation record, and this information plays a vital role in preparing optimized maintenance policies that maximize availability or minimize life cycle costs.
Keywords: Discrete event models; Discrete event system specification; Evaluation methodologies; Mission reliability; Object oriented model; Operating environment; Reliability Evaluation; Traffic signal controllers